(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
Underground waters in the volcanic zones are not directly reflected in the materials of long-range shooting. Analysis of aerospace photos shows that in volcanic regions the basic standards of prediction consist relief features. Thus, the use of aerospace materials let us reveal buried valleys, which can be associated with interlava and underlava water flows.